Analisis Pengaruh Perspektif Balanced Scorecard Terhadap Kinerja Perusahaan : Studi Kasus Pada Bank Konvensional Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023 - Fahmie, Arief; Viva, Firsa Nur; Gendalasari, Gen Gen (Program Vokasi dan LPPM IBI Kesatuan, 2025)
Conventional banks are still the financial institutions that dominate banking nationally. This dominance is seen from all aspects, such as the number of assets, the number of customers, and the reach of services. Despite that, the number of bank developments has decreased in 2019-2023. The decrease in the number of banks indicates problems such as increasing competition in the banking industry. Thus, conventional banks can find solutions to overcome their problems by measuring company performance. Currently, many companies still use traditional measurements that focus on financial aspects. Therefore, measuring company performance must innovate in a modern way by implementing the Balanced Scorecard approach. This study aims to determine the effect of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective on company performance in conventional banks listed on the Indonesia Stock Exchange for the period 2019-2023. This type of research uses quantitative descriptive. The data testing method in the study uses descriptives analysis and classical assumption tests consisting of normality tests, heteroscedasticity tests, multicollinearity tests, and autocorrelation tests. The data analysis method in this study is in the form of multiple linear regression analysis and hypothesis testing using several tests, including coefficient of determination (R²), T test, and F test. The results of the financial perspective test have a negative direction and have a significant effect on company performance in conventional banks listed on the Indonesia Stock Exchange for the period 2019-2023, while the results of the customer perspective, internal business process, learning and growth perspective have a negative direction and do not have a significant effect on company performance in conventional banks listed on the Indonesia Stock Exchange for the period 2019-2023. In addition, the results of the financial perspective test, customer perspective, internal business process perspective, learning and growth perspective simultaneously affect company performance in conventional banks listed on the Indonesia Stock Exchange for the period 2019-2023